The Toyota way : 14 management principles from the world's greatest manufacturer - Liker, Jeffrey K., ....- (New York : Mc Graw Hill, 2021)
The bestselling guide to Toyota's legendary philosophy and production system-updated with important new frameworks for driving innovation and quality in your business One of the most impactful business guides published in the 21st Century, The Toyota Way played an outsized role in launching the continuous-improvement movement that continues unabated today. Multiple Shingo Award-winning management and operations expert Jeffrey K. Liker provides a deep dive into Toyota's world-changing processes, showing how you can learn from it to develop your own improvement program that fits your conditions. Thanks in large part to this book, managers across the globe are creating workforces and systems that produce the highest-quality products and services, establish and retain customer loyalty, and drive business profitability and sustainability. Now, Liker has thoroughly updated his classic guide to include: Completely revised data and updated information about Toyota's approach to competitiveness in the new world of mobility and smart technology Illustrative examples from manufacturing and service organizations that have learned and improved from the Toyota Way A fresh approach to leadership models The brain science and skills for learning to think scientifically How Toyota applies Hoshin Kanri, a planning process that aligns objectives at all levels and marries them to business strategy Organized into thematic sections covering the various aspects of the Toyota Way-including Philosophy, Processes, People, and Problem Solving-this unparalleled guide details the 14 key principles for building the foundation of a powerful improvement system and managing it for ultimate competitive advantage. With The Toyota Way, you have an inspiration and a model of how to set a direction, continuously improve and learn at all levels, continually flow value to satisfy customers, improve your leadership, and get quality right the first time
Includes index.
Description based on print version record.
Keywords: Electronic books; Corporate culture; Industrial productivity; Production management -- Case studies